Factors Influencing Errors in Spoken Discourse and Effective Strategies for Management - Baldesanso-Demecillo, Ghie (EduLine: Journal of Education and Learning Innovation, 2025)
In spoken conversation, errors pose significant communication problems in various settings, including the workplace, the classroom, and everyday encounters. This study aimed to analyze the complex variables that lead to these types of mistakes and explore practical approaches to addressing them. The research employed a qualitative research design because it investigated factors influencing errors in spoken discourse and effective strategies for their management. The participants of this study were selected from Grade 9 students. They were chosen through purposive sampling. An audio-recorded interview focusing on participants' experiences with managing errors in spoken discourse, the effective strategies they employ, the challenges they face, and the contextual factors influencing their communication was the instrument used in the study. The study revealed that students lacked confidence in speaking due to the learning environment and psychological factors. They handled it through consistent practice, knowledge acquisition, and a positive mindset. Therefore, teachers and school administrators should foster a positive and supportive learning environment that encourages students to engage actively in the process of understanding and correcting errors. Lastly, teachers may implement activities that promote self-confidence, resilience, and a growth mindset in language learning.